Reference frames in virtual spatial navigation are viewpoint dependent - Török, Ágoston; Nguyen, T. Peter; Kolozsvári, Orsolya; Buchanan, Robert J.; Nadasdy, Zoltan (Frontiers in Human Neuroscience, 2014)
Spatial navigation in the mammalian brain relies on a cognitive map of the environment. Such cognitive maps enable us, for example, to take the optimal route from a given location to a known target. The formation of these maps is naturally influenced by our perception of the environment, meaning it is dependent on factors such as our viewpoint and choice of reference frame. Yet, it is unknown how these factors influence the construction of cognitive maps. Here, we evaluated how various combinations of viewpoints and reference frames affect subjects’ performance when they navigated in a bounded virtual environment without landmarks. We measured both their path length and time efficiency and found that (i) ground perspective was associated with egocentric frame of reference, (ii) aerial perspective was associated with allocentric frame of reference, (iii) there was no appreciable performance difference between first and third person egocentric viewing positions and (iv) while none of these effects were dependent on gender, males tended to perform better in general. Our study provides evidence that there are inherent associations between visual perspectives and cognitive reference frames. This result has implications about the mechanisms of path integration in the human brain and may also inspire designs of virtual reality applications. Lastly, we demonstrated the effective use of a tablet PC and spatial navigation tasks for studying spatial and cognitive aspects of human memory.